2015
DOI: 10.1007/82_2015_431
|View full text |Cite
|
Sign up to set email alerts
|

Tapping the Potential of DNA Delivery with Electroporation for Cancer Immunotherapy

Abstract: Cancer is a worldwide leading cause of death, and current conventional therapies are limited. The search for alternative preventive or therapeutic solutions is critical if we are going to improve outcomes for patients. The potential for DNA vaccines in the treatment and prevention of cancer has gained great momentum since initial findings almost 2 decades ago that revealed that genetically engineered DNA can elicit an immune response. The combination of adjuvants and an effective delivery method such as electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The situation improved upon combination of DNA vaccine injection and in vivo electroporation [EP, for review, see Ref. ( 105 )]. In vivo EP increased cellular DNA uptake leading to generation of more antigen available for immunisation and potentially made DNA more visible to the cytosolic innate sensors.…”
Section: Vaccine Platformsmentioning
confidence: 99%
“…The situation improved upon combination of DNA vaccine injection and in vivo electroporation [EP, for review, see Ref. ( 105 )]. In vivo EP increased cellular DNA uptake leading to generation of more antigen available for immunisation and potentially made DNA more visible to the cytosolic innate sensors.…”
Section: Vaccine Platformsmentioning
confidence: 99%
“…294,[372][373][374][375][376] In vitro and in vivo preclinical studies of this technique demonstrated skin entry of larger molecules, such as heparin (12 kDa), peptides, proteins (such as luteinizing hormone-releasing hormone), and nucleic acids, 260,[377][378][379][380] with potentially extensive use for investigational DNA vaccines in animals and humans. 194,381,382 Inovio's CELLECTRA series of electroporation devices 383 and Ichor's TriGrid delivery system 385 are capable of ID and IM delivery. A hollow needle injects the drug conventionally, while parallel solid needles surrounding the injected dose create the current to generate pores in the target muscle tissue.…”
Section: Needle-free Technologiesmentioning
confidence: 99%
“…[463][464][465][466][467][468][469][470] Research on and development of coated microarray patches for vaccination are also underway by many other groups. 340,381,471 Experimental placement of the solid microstructured transdermal system microarray patches device on human volunteers found it to be "well tolerated" and "nonintimidating and not painful." The Georgia Institute of Technology microarray patch (without coating) has been used in clinical studies to assess usability and completeness of skin penetration when applied by self-administration, and study participants indicated they would be more willing to be vaccinated with influenza vaccine if microarray patches were available.…”
Section: Needle-free Technologiesmentioning
confidence: 99%
“…Although DNA vaccines performed well in mice, the conditions of injection in patients differed and led to limited immunogenicity. Several approaches to improve immunogenicity of DNA vaccines have been developed [ 6 , 7 ]. An important strategy was to combine injection with in vivo electroporation (EP) which significantly improved immunogenicity by increasing cell transfection, leading to improved antigen expression and adjuvancy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%